Uporaba ekspertnega sistema za oceno in simuliranje strateškega položaja podjetij - Sagadin, Tone (Uporabna informatika (Ljubljana), 1994)
The article presents the application of expert system which enables a complex evaluation of enterprise strategic position including the following aspects: macroeconomic environment, industry attractiveness, competitive ability and economic strength. On this basis it is possible to define a complex evaluation of enterprise strategic position from which also results a plan of future business strategy, with the possibility of simulating different alternatives.
Keywords: ekspertni sistemi; podjetje; poslovna strategija